Implikasi Media Pembelajaran Digital Google Meet Terhadap Kompetensi Profesional Guru Pendidikan Agama Islam (Studi Di SMPN 2 Garut) - Salamudin, Ceceng; Hikam, Muhamad Bani; Abdullah, Deba Muslim (STAI Al-Musaddadiyah Garut, 2023)
This study is motivated by the observation that some teachers face challenges in their professional competencies, particularly in their proficiency with technology as a teaching medium. As a result, there is a need to enhance these teachers' capabilities through the use of Google Meet as a solution to improve their ability to meet professional teaching standards. The objectives of this research are: (1) To assess the professional competence of Islamic Religious Education (PAI) teachers at SMPN 2 Garut. (2) To examine the use of Google Meet as a digital learning medium at SMPN 2 Garut. (3) To evaluate the implications of using Google Meet on the professional competence of teachers at SMPN 2 Garut. This study employs a field-based qualitative research method. The primary data sources include interviews with PAI teachers at SMPN 2 Garut, while secondary data sources comprise books and other literature relevant to this research. Data collection techniques include observation, interviews, and documentation. The data analysis technique follows the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The findings of this research indicate that the use of Google Meet as a digital learning medium positively impacts teachers' professional competencies. A teacher's ability to effectively utilize technology contributes to their qualification as a professional educator. These are the key findings derived from this study. Keywords: digital learning media, Google Meet, professional competence of teachers